1987
DOI: 10.1161/01.str.18.6.1074
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow in normal pressure hydrocephalus.

Abstract: A xenon-133 method was used to measure cerebral blood flow (CBF) before and after cerebrospinal fluid (CSF) removal in patients with normal pressure hydrocephalus (NPH). Preliminary results suggested that shunting should be performed on patients whose CBF increased after CSF removal. There was a significant increase in CBF in patients with NPH, which was confirmed by the favorable outcome of 88% of patients shunted. The majority of patients with senile and presenile dementia showed a decrease or no change in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 31 publications
1
45
1
Order By: Relevance
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by the inhalation method or single photon emission computed tomography (SPECT) utilizing radio-labeled materials including xenon-133, 70,[74][75][76]117) technetium-99m hexamethylpropyleneamine oxime ( 99m Tc-HMPAO), 54B) nonradioactive xenon-CT, 118) and positron emission tomography (PET) with [ 15-O]H 2 O. 82,90) In a study measuring CBF in 31 patients of suspected Chapter 1: Diagnosis iNPH with 99m Tc-HMPAO SPECT, 54B) reduced blood flow over a wide area, especially in the cortex and subcortical white matter of the frontal and temporal lobes (expansion of central low-flow area), is seen.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by the inhalation method or single photon emission computed tomography (SPECT) utilizing radio-labeled materials including xenon-133, 70,[74][75][76]117) technetium-99m hexamethylpropyleneamine oxime ( 99m Tc-HMPAO), 54B) nonradioactive xenon-CT, 118) and positron emission tomography (PET) with [ 15-O]H 2 O. 82,90) In a study measuring CBF in 31 patients of suspected Chapter 1: Diagnosis iNPH with 99m Tc-HMPAO SPECT, 54B) reduced blood flow over a wide area, especially in the cortex and subcortical white matter of the frontal and temporal lobes (expansion of central low-flow area), is seen.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…These findings are supported by other studies. 57,70,74,76,117,128) A PET study reported the mean CBF decreased in the cerebrum and cerebellum with regional decrease in the basal ganglia and thalamus but not in the white matter. 82) There are few studies supporting the correlation between reduced flow and degree of symptoms.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 2 more Smart Citations
“…9 The literature, however, indicates that whereas a direct correlation between reduced CBF and ventricular size has been suggested in some studies, 10,11 others have refuted this finding. 12, 13 Mathew et al 14 suggested that dilation of the ventricular system stretches the anterior cerebral arteries over the corpus callosum, thereby reducing flow. Ventricular dilation has also been suggested to increase intraparenchymal pressure and directly compress the capillary bed or venous drainage.…”
mentioning
confidence: 99%